Warming altered the effect of cold stratification on the germination of Spartina alterniflora across climatic zones in its invasive range - Wu, Fujia; Chen, Xincong; Guo, Yangping; Liu, Wenwen; Zhang, Yihui (Frontiers in Plant Science, 2024)
Introduction Cold stratification has a pronounced influence on seed germination, climate change is altering cold stratification regimes across climatic zones. Therefore, it is urgent to explore how seed germination from different geographic provenances responds to these changes. The invasive plant Spartina alterniflora spans three climatic zones along the Chinese coast, such distribution provides a natural temperature gradient to explore how warming alters the effects of cold stratification on germination. Methods Spartina alterniflora seeds were collected from nine locations across three climatic zones in China from September to November in 2021. Seeds were planted in three common gardens with three latitude gradients of 21 °N, 28 °N, and 38 °N, after 0-month and 4-month cold stratification at 4 °C in November 2021 and March 2022, respectively. Each common garden simulated the natural temperature conditions and shield the plants from rain. Results Results showed that cold stratification led to explosive germination and rapidly reaching a plateau, shortened the germination time and improved the final germination rate. These effects were magnified from the high-latitude garden to the low-latitude one (i.e., warming). And the interactive effect of cold stratification and warming varied among provenances. For the subtropical and temperate provenances, the improvement in germination rate induced by cold stratification gradually increased from high-latitude garden to low-latitude one, while for tropical provenances, this difference progressively decreased. Discussion: Thus, our results indicated that subtropical and temperate provenances may migrate northward for adequate low temperatures to ensure high germination rate, because cold stratification can alleviate the negative impacts of warming on germination. For the tropical provenances, warming also suppressed the advantage that cold stratification provides in enhancing the germination rate, which may hinder their further spread southward. Our study contributes to understanding the responses of vegetation germination and recruitment across different climatic zones under global warming, providing insights for the distribution of cosmopolitan species and the management of exotic species.